The effect of digital marketing on organizational agility of SACCOs in Meru Town (African Journal of Science, Technology and Social Sciences, 2024)
Savings and Credit Cooperative Organizations (SACCOs) are vital drivers of economic growth in the country. SACCOs provide financial services, including deposits, loans, savings accounts, money transfers, insurance, and payment services. Even though digital media exists to improve the flexibility and the speed of business processes to improve organizational agility, its aspects are a very recent phenomenon among Savings and Credit Cooperative Organizations. An empirical inquiry was relevant to understand the domain of communication, marketing strategies, and its influence on organizational agility since the discourse of digital marketing is continuously developing. SACCOs must understand the association of digital marketing to organizational agility to embrace digital technology in their operations and stay relevant to their members while increasing their level of business resilience. The study sought to determine the effect of digital marketing (social media, mobile, and website marketing) on the organizational agility of SACCOs in Meru Town, Kenya. A descriptive research design was adopted to gather information on the relationship between the two research variables. With a target population of 5 SASRA-licensed SACCOs in Meru Town, data was collected using a semi-structured questionnaire where a stratified sampling method was utilized to attain the desired representation target population of 52 respondents. A pilot test was conducted to check the reliability and validity of the questionnaire adopted as the research instrument. The data was tabulated and analyzed using descriptive and inferential statistics, whereby tabular, graphical, and numerical representations were utilized. Multiple linear regression was conducted to establish the inferential statistics and define the relationship between digital marketing indicators and organizational agility. The study results established that social media marketing, mobile marketing, and website marketing are positively related to the organizational agility of SACCOs. A coefficient of determination (R-squared) of 0.180 indicated that approximately 18% of the variance in organizational agility could be accounted for by the combination of social media, mobile, and website marketing strategies. The moderate level of explanatory power implies that while the chosen predictors are relevant, other factors likely influence SACCOs' organizational agility. The study's outcomes encourage decision-makers to embrace a comprehensive approach that integrates digital strategies into a wider organizational transformation and adaptation framework. The study's findings contribute to the growing body of knowledge regarding the intersection of digital marketing strategies and organizational agility. The study’s results emphasize that the benefits of these strategies extend beyond mere technological implementation, reflecting a fundamental shift in how organizations engage with their ecosystem, respond to changes, and navigate uncertainties.
Keywords: Digital marketing; Organizational Agility; Saccos; Social media marketing; Website Marketing